Alternativa röster: Radions kvinnoprogram som offentliga normbrytare - Nordberg, Karin (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2004)
Actual changes of the programme tables on Swedish Radio have reduced women's programmes by half of its emission time, at the same time as news broadcasting continues to expand. Fresh statistics show that women's representation in news programmes during the last two years has broken an earlier upward moving trend. According to the masculine profile of news logic, the author asks what the meaning of these policy changes might be in gender terms, and how programming should be organized to promote women's voices and interests in the media. With examples from three programmes — "Housewife hour" in the 1940:s, "Radio Ellen" in the 1980:s and "Freja" in the 2000:s — female strategies of resistance and rhetorics are presented and discussed, and related to different theoretical gender aspects. More research is needed, though, to judge the effects of the strategies and the relevance of the theories.